THE ETYMOLOGICAL ANALYSIS OF "SCIENCE" PHRASEOLOGICAL UNITS IN FRENCH PHRASEOLOGY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article focuses on the etymological analysis of phraseological units related to "science" in the French language. It examines the linguistic roots, historical evolution, and semantic transformations of these units, emphasizing their connection to cultural and scientific traditions. The study explores the adoption of Latin and Greek elements, their integration into modern scientific discourse, and their cultural and linguistic features. This analysis highlights the interconnectedness of language and scientific thought within the French intellectual tradition.